The Impact of Human Capital on Shadow Economy in Indonesia - Saraswati Saraswati; Neli Agustina (Economics and Finance in Indonesia, 2020)
Shadow economy is a market for legal and illegal goods and services that escape recording and estimation of GDP. It can cause inaccurate estimation of GDP, declining tax revenue, and less precise economic policies. Improving the quality of human capital, both in education and health dimensions, can reduce shadow economy. The research aims to estimate shadow economy and analyze the influence of the quality of human capital on shadow economy in Indonesia. Applying time series multiple linear regression analysis, the findings show that the average shadow economy in Indonesia is 28.97 percent, changes in life expectancy negatively affect changes in shadow economy, while changes in the gross participation rate of tertiary education have a positive effect.